Primary health care providers' views on managing substance use among people living with HIV - Ramprakash Kaswa; Marietjie de Villiers (AOSIS, 2023)
Background: The growing culture of substance use among people living with human immunodeficiency virus (PLWH) is a serious threat to the human immunodeficiency virus (HIV) pandemic. As the gatekeepers of comprehensive care, primary care providers are responsible for screening, assessing, and managing individuals who use substances. Aim: This study aimed to evaluate primary care providers' views and approaches to substance use management among PLWH who attend primary care services in Mthatha. Setting: This study was conducted at Ngangelizwe and Mbekweni Community Health Centres (CHCs) in the Eastern Cape province's King Sabata Dalindyebo (KSD) sub-district municipality. Methods: This qualitative phenomenological study involved the views of primary care providers. This study included 32 primary health care (PHC) providers. All participants were female except one male with a mean age of 48.6 years (range 27-64 years). Semi-structured interviews were conducted until saturation of the theme was reached. Then, the data from the transcribed interview were analysed with a thematic framework. Results: Substance use among PLWH was reported to be associated with poor clinical outcomes and disruption of antiretroviral therapy (ART) adherence. The significant barriers reported for substance use management in PHC settings were a lack of resources, skilled providers and poor community participation. Conclusion: Substance use management programmes are not commonly offered in PHC because of the lack of human and infrastructural resources, the lack of skilled providers and poor community engagement. Contribution: This study provides a context-specific PHC providers' approach to substance use management.